1993
DOI: 10.1037/h0101171
|View full text |Cite
|
Sign up to set email alerts
|

"Common factors" and "nonspecific variables": Clarification of the two concepts and recommendations for research.

Abstract: In the field of psychotherapy, the terms "common factors" and "nonspecific variables" are generally perceived as synonyms. However, the indiscriminate use of these concepts imposes major restrictions on understanding the factors that cut across different forms of intervention: it implicitly confines them to undefined aspects of the therapeutic relationship. In this article, an attempt is made to understand why the association or blending of the two concepts is still predominant. It is argued that the term comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 84 publications
(96 reference statements)
1
60
0
2
Order By: Relevance
“…Though the term "common factors" has become increasingly popular, an alternative has also been present in the field: "nonspecific factors." While some authors have used the terms nonspecific and common interchangeably to refer to the construct we intend, "nonspecific" has additional meanings beyond "common," and at times some authors have used it to mean those elements of psychotherapy that are either somehow unspecified at present, inherently unspecifiable and therefore unobservable, or else elements of therapy that are auxiliary to the technical variables that are primarily responsible for producing therapeutic effects (Castonguay 1993). Many authors have suggested that since these statements are not generally true of the common factors anymore, the term "nonspecific" should be dropped from the lexicon entirely (e.g., Castonguay 1993;Castonguay and Grosse Holtforth 2005;Lampropoulos 2000;Omer and London 1989;Weinberger and Rasco 2007).…”
Section: Common Vs "Nonspecific" Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Though the term "common factors" has become increasingly popular, an alternative has also been present in the field: "nonspecific factors." While some authors have used the terms nonspecific and common interchangeably to refer to the construct we intend, "nonspecific" has additional meanings beyond "common," and at times some authors have used it to mean those elements of psychotherapy that are either somehow unspecified at present, inherently unspecifiable and therefore unobservable, or else elements of therapy that are auxiliary to the technical variables that are primarily responsible for producing therapeutic effects (Castonguay 1993). Many authors have suggested that since these statements are not generally true of the common factors anymore, the term "nonspecific" should be dropped from the lexicon entirely (e.g., Castonguay 1993;Castonguay and Grosse Holtforth 2005;Lampropoulos 2000;Omer and London 1989;Weinberger and Rasco 2007).…”
Section: Common Vs "Nonspecific" Factorsmentioning
confidence: 98%
“…While some authors have used the terms nonspecific and common interchangeably to refer to the construct we intend, "nonspecific" has additional meanings beyond "common," and at times some authors have used it to mean those elements of psychotherapy that are either somehow unspecified at present, inherently unspecifiable and therefore unobservable, or else elements of therapy that are auxiliary to the technical variables that are primarily responsible for producing therapeutic effects (Castonguay 1993). Many authors have suggested that since these statements are not generally true of the common factors anymore, the term "nonspecific" should be dropped from the lexicon entirely (e.g., Castonguay 1993;Castonguay and Grosse Holtforth 2005;Lampropoulos 2000;Omer and London 1989;Weinberger and Rasco 2007). As we will see, increasing evidence supports several common factors as specific contributors to the therapeutic process which have been identified, isolated, and sometimes manipulated, and the use of the term "nonspecific" to describe them constitutes an undeserved continued belittling of these important therapeutic elements.…”
Section: Common Vs "Nonspecific" Factorsmentioning
confidence: 98%
“…Even in outcome investigations that do not employ a placebo condition but instead contrast two or more interventions (experimental or control), the potential effects of "nonspecific" or "common" factors (see Castonguay, 1993) must still be equated across conditions to prevent confounding the outcome of group comparisons. We must ensure that factors putatively involved in what used to be called placebo (e.g., contact with a therapist, suggestion effects, client expectancy for improvement, demand characteristics in the assessment situation that encourage displays of improvement, and the therapeutic relationship) are still held constant among all conditions in which some form of intervention is being administered.…”
Section: Problems With Placebo Conditionsmentioning
confidence: 99%
“…Gemäß Frank und Frank [1993] stellen die Emotionen in der Therapie eines der sechs Elemente dar, die allen therapeutischen Verfahren gemein sind. Gleichermaßen betrachten Goldfried [1980] und auch Castonguay [1993;Castonguay et al, 1996] Henry, 1977Henry, , p 1053. Auch von einer konkreten Umsetzung der «Placebo-Therapie» [Fish, 1973] zu sprechen, liegt hier nicht fern.…”
Section: Fortsetzungunclassified